2013
DOI: 10.1007/s00586-013-2967-2
|View full text |Cite|
|
Sign up to set email alerts
|

Parameters influencing the outcome after total disc replacement at the lumbosacral junction. Part 2: distraction and posterior translation lead to clinical failure after a mean follow-up of 5 years

Abstract: Purpose The aim of the second part of the study was to investigate the influence of parameters that lead to increased facet joint contact or capsule tensile forces (disc height, lordosis, and sagittal misalignment) on the clinical outcome after total disc replacement (TDR) at the lumbosacral junction. Methods A total of 40 patients of a prospective cohort study who received TDR because of degenerative disc disease or osteochondrosis L5/S1 were invited to an additional follow-up for clinical (ODI and VAS for ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Why fewer of the TDR group were working at 5 years is not understood, as in the TDR group 59 % were totally pain free, compared with only 38 % in the fusion group. Two other papers adjacent to this dealt with the likelihood, for biomechanical reasons of TDR failure at the lumbosacral level [46,47]. In doing a TDR at the lumbosacral level with marked narrowing of the disc, one must avoid increasing segmental lordosis, and posterior translation of the superior vertebrae.…”
Section: Disc Replacement and Fusionmentioning
confidence: 99%
“…Why fewer of the TDR group were working at 5 years is not understood, as in the TDR group 59 % were totally pain free, compared with only 38 % in the fusion group. Two other papers adjacent to this dealt with the likelihood, for biomechanical reasons of TDR failure at the lumbosacral level [46,47]. In doing a TDR at the lumbosacral level with marked narrowing of the disc, one must avoid increasing segmental lordosis, and posterior translation of the superior vertebrae.…”
Section: Disc Replacement and Fusionmentioning
confidence: 99%
“…These observed increases agree with our second hypothesis. Thus, these predicted high loads might explain the clinical results of Strube et al (2013a), who demonstrated that an iatrogenic overdistraction is significantly associated with clinical failure after TDR. Furthermore, Leivseth et al (2006) showed that the amount of distraction is typically larger in L5-S1 than in L4-5, which might partially explain the unsatisfactory clinical results of a TDR in the lumbosacral segment L5-S1 (Siepe et al, 2008(Siepe et al, , 2007.…”
Section: Cc-position (Mm)mentioning
confidence: 91%
“…Furthermore, Leivseth et al (2006) showed that the amount of distraction is typically larger in L5-S1 than in L4-5, which might partially explain the unsatisfactory clinical results of a TDR in the lumbosacral segment L5-S1 (Siepe et al, 2008(Siepe et al, , 2007. The complete postoperative RoM in the sagittal plane (sum of the RoF and RoE) was measured in patients in several clinical studies, and a direct correlation with the resultant clinical outcome was investigated (e.g., Johnsen et al, 2013;Leivseth et al, 2010;Leivseth et al, 2006;Siepe et al, 2009;Strube et al, 2013a). However, the resultant complete RoM appears to be insensitive to detecting the elementary mechanical changes shown herein (Fig.…”
Section: Cc-position (Mm)mentioning
confidence: 97%
See 2 more Smart Citations